Cost-effectiveness of first-line induction and maintenance treatment sequences in non-squamous non-small cell lung cancer (NSCLC) in the U.S. Issue 3 (September 2015) - Kumar, Gayathri; Woods, Beth; Hess, Lisa M.; Treat, Joseph; Boye, Mark E.; Bryden, Peter; Winfree, Katherine B.
Highlights Clinicians have a range of therapeutic options for non-squamous non-small cell lung cancer. A cost-effectiveness analysis was conducted according to ISPOR standards. Depending on the decision maker threshold, several treatment strategies may be cost effective. Results were consistent across multiple sensitivity analyses.